Microanalytical study of the fresco 'the good and the bad judge' in the medieval village of Monsaraz (Southern Portugal). (24th April 2013) - Gil, M.; Araujo, C.; Carvalho, M.L.; Longelin, S.; Dias, L.; Valadas, S.; Souto, C.; Frade, J.; Ribeiro, I.; Mirão, J.; Candeias, A.; Streli, Christina; et al.
<x xml:space="preserve">Abstract</x> This article describes a study carried out on the emblematic mural painting so‐called 'fresco of the good and bad judge' located at the medieval village of Monsaraz (southern Portugal). This painting, with two distintic narratives, is thematically unique in Portugal and rare in the context of European Renaissance art. Scientific research was undertaken to clarify doubts about the chronology of the two painted scenes through a technical study and a material characterization of its constituents, namely, mortars, pigments, and binders. Elemental and chemical analyses were performed by scanning electron microscopy with energy‐dispersive X‐ray spectroscopy detector, optic microscopy, μ‐Raman spectroscopy and Fourier transform infrared microspectroscopy. Comparative examination revealed that along with the stylistic similarities, there are no recognizable differences in the painting technique (garments and carnations) nor in the structure and composition of the pictorial support and chromatic layers. The mortars of both scenes are made of lime with different ratios of calcium (Ca) and magnesium (Mg) mixed with siliceous and granitic aggregates. An intonachino made with a more calcitic lime is visible in all carnations. The pigments identified in both scenes were mercury sulfide (HgS), red and yellow ochres (Fe2O3 and FeO(OH) as chromophores), carbon black (C) and azurite (2CuCO3.Cu(OH)2). The extensive areas of chromatic losses seem to indicate that a mixed pictorial technique was used by the artist (fresco and secco). Copyright © 2013 John Wiley & Sons, Ltd.